Gummiklipp som skyddslager i en vägkonstruktion i ett fullskaleprojekt - Edeskär, Tommy (Luleå tekniska universitet, Geoteknologi, 2004)
Tyre shreds have been used as construction material in foundation engineering applications about 30 years, mainly in North America. Tyre shreds have interesting technical properties for foundation engineering applications such as low density, high draining capacity, and thermal isolation capability. In Europe the experiences are few in using tyre shreds in foundation engineering work. In this project tyre shreds have been used as capping layer for thermal insulation purposes in a test section of the national road 686 outside the city of Boden in northern Sweden. The road was reconstructed and paved in order to increase the bearing capacity. A 600 mm thick tyre shred layer was used as thermal insulation underlaying the sub-base material. The test site is divided into three test sections. In test section P1 crushed rock is used as sub-base material and in test section P2 air blast furnace slag as sub-base material. The third test section is used as a reference and consists of crushed rock as sub-base material without underlaying capping layer. The main objectives of the test site are to gain experience in using tyre shreds as a construction material, study the capacity of thermal insulation of the material and to study how to design the superstructure when using tyre shreds using the Swedish design practise for flexible pavement. Gummiklipp från uttjänta bildäck har använts som konstruktionsmaterial i anläggningstekniska sammanhang i 30 år, främst i Nordamerika. Gummiklipp har intressanta tekniska egenskaper som låg densitet, hög dränerande kapacitet och hög tjälisolerande förmåga. I Europa är erfarenheterna få avseende användande av materialet vid markbyggande. I detta projekt har gummiklipp använts som material i skyddslager i en provsträcka vid ombyggnation av väg 686 i Bodens kommun. Provsträckan består av tre delsträckor, en med bergkross (P1) och en med hyttsten (P2) som förstärkningslager. Den tredje delsträckan, referenssträckan, består av bergkross som förstärkningslager utan något underliggande ...